From Care-less to Care-full: Education for Citizenship in Schools and Beyond - Tupper, Jennifer A. (Alberta Journal of Educational Research, 2007)
This article attempts to disrupt liberal democratic understandings of citizenship as they inform social studies curricula in schools. Care-less citizenship is used throughout the article to describe the denial or propensity to ignore the deep inequities that exist in the world. The article also implicates schooling, and in particular social studies education, in the maintenance of citizenship as a falsely universalized construct through such practices as standardization and high-stakes testing. Conceptions and experiences of citizenship articulated by five secondary social studies teachers and 10 preservice teachers provide a means through which to improve understanding of how students are constructed as citizens in relation to the prescribed and negotiated curriculum encountered in classrooms. Finally, the article advances an understanding of citizenship as care-full—that is, attentive, relational, and caring—in which conditions of oppression operating to limit the realization of equity are continual subjects of interrogation.